Relevance Of National Literacy Movement, School Literacy Movement With Strengthening Character Education On MI Subject Matter (Study of MOEC Regulation Number 23 Year 2015 With Presidential Regulation No. 87 of 2017) - Fifi Aris Wulandari (AIUA Journal of Islamic Education, 2020)
The issue of education is one area that is often seen as very vital and decisive in the field of government. One of the problems in education is the decline in the quality of reading among students. Indonesia has the lowest ability in the PISA and TIMSS competitions. This certainly requires innovation and creativity that can encourage the spirit of students to read especially at the Elementary School level. The method used in this paper is the study of literature. The Ministry of Education and Culture through Ministerial Regulation number 23 of 2015 launche an education policy. Educational policy in the form of the National Literacy Movement which has 3 domains, one of which is the School Literacy Movement to foster noble character towards students through language which is the first step to creating a culture of literacy and students' interest in reading. School Literacy Movement is more than just reading and writing but includes thinking skills according to the stages and components of literacy. The school literacy movement is expected to be able to bring change both in terms of behavior, attitudes and responsibilities as well as instilling and growing the values of the nation's character that is religious, nationalism, independent, mutual cooperation, and integrity in elementary school students. The character values are contained in Permendikbud Number 87 of 2017 concerning Strengthening Character Education (PPK). The National Literacy Movement, the School Literacy Movement is very closely related to the Strengthening of Character Education, in the implementation of the School Literacy Movement in schools and the Strengthening of Character Education has not been running optimally but can run when the school institutions and students are active.